Amino acid-based deep eutectic solvent as a versatile catalyst for the green synthesis of chromenopyrimidines - Afagh Ranjbaran; Davood Habibi; Arezo Monem; Nastaran Dehnokhalaji (Scientific Reports)
Abstract A novel deep eutectic solvent (Thr/Mal-DES) was synthesized by mixing one mole of L-threonine (Thr) with one mole of malonic acid (Mal) and was characterized by FT-IR, 1H NMR, TGA/DTA, and densitometry techniques. Then, it was used as a highly effective catalyst for the rapid synthesis of chromeno[4,3-d]pyrimidines from the reaction of 4-hydroxy-coumarin, urea/thiourea and aldehyde under solvent-free conditions at 80 °C in high yields and short reaction times.